Alterations in the neuropeptide galanin system in major depressive disorder involve levels of transcripts, methylation, and peptide - Barde, Swapnali (Proc Natl Acad Sci U S A, 2016)
Major depressive disorder (MDD) is a substantial burden to patients, families, and society, but many patients cannot be treated adequately. Rodent experiments suggest that the neuropeptide galanin (GAL) and its three G protein-coupled receptors, GAL(1–3), are involved in mood regulation. To explore the translational potential of these results, we assessed the transcript levels (by quantitative PCR), DNA methylation status (by bisulfite pyrosequencing), and GAL peptide by RIA of the GAL system in postmortem brains from depressed persons who had committed suicide and controls. Transcripts for all four members were detected and showed marked regional variations, GAL and galanin receptor 1 (GALR1) being most abundant. Striking increases in GAL and GALR3 mRNA levels, especially in the noradrenergic locus coeruleus and the dorsal raphe nucleus, in parallel with decreased DNA methylation, were found in both male and female suicide subjects as compared with controls. In contrast, GAL and GALR3 transcript levels were decreased, GALR1 was increased, and DNA methylation was increased in the dorsolateral prefrontal cortex of male suicide subjects, however, there were no changes in the anterior cingulate cortex. Thus, GAL and its receptor GALR3 are differentially methylated and expressed in brains of MDD subjects in a region- and sex-specific manner. Such an epigenetic modification in GALR3, a hyperpolarizing receptor, might contribute to the dysregulation of noradrenergic and serotonergic neurons implicated in the pathogenesis of MDD. Thus, one may speculate that a GAL(3) antagonist could have antidepressant properties by disinhibiting the firing of these neurons, resulting in increased release of noradrenaline and serotonin in forebrain areas involved in mood regulation.